The uncomfortable question of urgency for liberal thought: A dialogue between John Locke’s Two Treatises of Government and contemporary liberal theory - Burbidge, D (Clarion Review, 2017)
Amartya Sen and Thomas M. Scanlon confront liberal theories of primary goods by asking how they determine the appropriate political urgency for some goods over others. Their review of arguments of welfare optimization through impartial reasoning reveals a lack of discussion on why in a democracy some citizen views should be considered objective and some subjective and to be pursued with less urgency. The article traces this disjuncture to discussions in John Locke’s Two Treatises of Government and argues that these contemporary difficulties are reflective of original irreconcilability between Locke’s political anthropology and social contract accounts. The first of these recommends gradual care in transitioning from family-based authority to the larger community, shedding light on the status of individuals regardless of formal political constitution. The second instead centres on political legitimacy through means of social contract, relying on assumptions of universal rationality that work against the first account’s deference to gradualism and parental authority. Here is where irreconcilability arises, for Locke’s is a theory that appreciates value in the slow and steady that is justified, in the end, in terms of uniform rational capacities. Whilst the conflicting emphases retain some sense of balance in Locke, contemporary liberal theories take only the second account forward, and so are incapable of debating appropriate political urgency.